Phenothiazine-functionalized push–pull Zn porphyrin photosensitizers for efficient dye-sensitized solar cells. Issue 11 (22nd January 2016) - Qian, Xing; Lu, Lin; Zhu, Yi-Zhou; Gao, Huan-Huan; Zheng, Jian-Yu
Abstract : A series of zinc porphyrin dyes (JY24–27 ) featured phenothiazine moieties have been synthesized and applied as photosensitizers in dye-sensitized solar cells. Abstract : A series of zinc porphyrin dyes (JY24–27 ) featured phenothiazine moieties have been synthesized and applied as photosensitizers in dye-sensitized solar cells. The phenothiazine donors were directly attached to the meso -position of porphyrins, and different π-linkers (benzene, thiophene and ethynyl benzene) and acceptor groups (carboxylic acid and cyanoacrylic acid) were applied to tune the photoelectric properties of these push–pull porphyrin dyes. The photophysical, electrochemical and theoretical studies revealed that the synthesized porphyrin dyes were all capable of being used as photosensitizer. The dyeJY27 with an extended conjugation by introducing ethynyl group exhibited a broader absorption region and more significantly improved IPCE values between 550 and 750 nm than the other three dyes, which ensured a good light-harvesting ability and a high short-circuit current density of 15.3 mA cm −2 . Finally, JY27 -based cell achieved a high efficiency of 6.25% under standard simulated irradiation.